The first results of remote mammographic breast cancer screening in Surkhandarya region (Texas Journal of Medical Science, 2024)
The widespread introduction of mammographic screening for early detection of breast cancer in the world has reduced the mortality rate of women from this disease in the general population by 20-30%. For many years, different standard mammographic screening methods have been used in the United States and many European countries, the principles of which are the same. It is common practice to standardize the X-ray mammography process and mammography characteristics in order to divide all healthy screened women into groups requiring different monitoring recommendations after the first mammogram. Viewing mammograms by two radiologists is considered recognized in the world to reduce the number of erroneous conclusions. In connection with the adoption of the law on medical examination of the population of the Republic of Uzbekistan, which provides for mammography for women after 45 years of age once a year, the question arises of standardizing this process in order to reduce breast cancer mortality in the regions of the Republic of Uzbekistan.